Solusi Eksak Sistem Imun Terhadap Virus Ebola - Aisyiyah, Amadhea Aisyatul; Widayani, Heni; Herawati, Erna (Jurnal Riset Mahasiswa Matematika, 2023)
The Ebola virus is a deadly disease that causes blood clots in the body's organs and is spread through direct contact with the blood or body fluids of sufferers. Based on this, the immune system in the body will continue to decrease and cause Ebola Hemorrhagic Fever. The 2014-2016 Ebola outbreak in West Africa has accelerated the development of several preventive vaccines against the Ebola virus. The goal of the vaccination is to induce immunity against infectious diseases. And also to stimulate the immune system and its ability to store and remember information about specific pathogens, leading to long-term protective immunity. The model equation for the Ebola virus vaccine in this study involves the concentration of the antigen which is a variable , by means of which the vaccine is inserted into the patient's body where it will attach to B memory cells which are variable , which will then be stimulated by the cells short-lived antibodies are denoted by variables  or long-lived cells are denoted by variables , while antibodies will prove efficacy denoted by variables  on the patient's immune response. The simulation of the exact solution for the Ebola vaccine uses the integration factor method which will later be compared with numerical simulations according to the parameter values from the research of Irene Balelli et al (2020). The simulation obtained has a very small calculation error value for each variable, which means that the exact value of the Ebola virus vaccination model shows that there is no significant difference to the numerical solution using the order 45 Rungge Kutta method, the largest resulting numerical error is 2.29640283510782×〖10〗^9.